The repeat length of C9orf72 is associated with the survival of amyotrophic lateral sclerosis patients without C9orf72 pathological expansions - Tang, Lu; Chen, Lu; Liu, Xiaolu; He, Ji; Ma, Yan; Zhang, Nan; Fan, Dongsheng (Frontiers in Neurology, 2022)
Objective: To explore whether the repeat lengths of C9orf72 gene and ATXN2 gene in ALS patients without C9orf72 repeat expansions confer a risk of ALS or survival disadvantages in ALS . Methods: We screened a hospital-based cohort of Chinese patients with sporadic ALS without C9orf72 repeat expansions and neurologically-healthy controls for C9orf72 GGGGCC and AXTN2 CAG repeat length to compare the frequency of possible detrimental length alleles using several thresholds. Furthermore, the clinical features of ALS were compared between ALS patient subgroups using different length thresholds of maximum C9orf72 and ATXN2 repeat alleles, including sex, age of onset, diagnostic delay, and survival. Results: Overall, 879 sporadic ALS patients and 535 controls were included and the repeat lengths of C9orf72 and ATXN2 were both detected. We found significant survival differences in patients using a series of C9orf72 repeat length thresholds from 2 to 5, among which the most significant difference was at the cut-off value of 2 (repeats 2 vs >2: median survival 67 months vs 55 months, log-rank p=0.032). Furthermore, Cox regression analysis revealed the role of age of onset (hazard ratio 1.04, 95% CI 1.03-1.05, p<0.001), diagnostic delay (0.95, 0.94-0.96, p<0.001), and carrying C9orf72 repeat length of 2 (0.72, 0.59-0.89, p=0.002) in the survival of patients without C9orf72 repeat expansions. In addition, bulbar onset was associated with poorer survival when the patients carried the maximum C9orf72 repeat allele over 2 (1.81, 1.32-2.48, p<0.001). However, no survival difference was found when applying a series of continuous cut-off values of ATXN2 or stratified by C9orf72 repeats of 2. Conclusion: The length of 2 in the maximum C9orf72 repeat allele was identified to be associated with favorable survival in ALS patients without C9orf72 repeat expansions. Our findings from the clinical setting implicated the possible cut-off definition of detrimental C9orf72 repeats, which should be helpful in the understanding of genetics in ALS and in clinical genetic counselling.